Suicidality and religiosity among patients with depressive and bipolar disorders: a cross-sectional North African study - Omar El Oumary; Laila Lahlou; Zineb Salehddine; Mina Ouhamou; Hicham Laaraj; Raymond Tempier; El Mostafa Bouattane; Jalal Doufik; Khalid Mouhadi; Mohamed Merzouki; Said Boujraf; Ismail Rammouz (Cogent Psychology)
Introduction: From the beginning of suicide research by Durkheim (1897); the relationship between religiosity and suicidal risk has been seen as a crucial issue. During the last decade, studies on this question have given variable results. However, such studies became a gateway to multiple questions, not only on the relationship between religion and suicide risk but more specifically among patients with depressive disorders, in particular. This study’s main objective is to assess the influence of religiosity on suicidal ideation; suicidal intentionality and on the severity of depressive symptoms in patients with depressive disorders diagnoses or bipolar depression episodes. We carried out an observational, descriptive, and analytical study of 324 patients with a current diagnosis of a major depressive disorder or a bipolar depressive episode. Patients were all Muslims and were interviewed using the Beck Depression Inventory; Suicide Intent Scale and Mini International neuropsychiatric interview Suicide Risk. The religiosity was assessed using the BIAC (Belief Into Action) adapted to Muslims in Morocco. We found that higher religiosity scores were associated with older age (>50 years), marriage, no negative impact of depression on work, presence of bipolar depression, and regularity of medical follow-up. Similarly, higher scores of religiosity were associated with lower scores of depression, suicidal intentionality, or suicidal risk. It will be useful to compare our results with other published results to appraise the positive impact of religiosity on reducing suicidal ideation and behavior among different populations, regardless of their religious affiliations.